2020
DOI: 10.5539/jas.v12n8p265
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception of Nanotechnology Among Students of Agricultural Faculties’ in Jordan

Abstract: This study investigated Knowledge and Perception of Nanotechnology among Students of Agricultural Faculties’ in Jordan. The research was based on distributing a questionnaire. This study collected data from 485 respondents, of which 410 were analyzed. The results revealed that a very significant finding that the majority of the investigated students (45%) have already heard the word ‘nanotechnology’, though (72%) of those (45%) do not know about nanotechnology very well. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Public perceptions of nanotechnology were investigated through surveys distributed to a representative sample of a national population worldwide. Studies of public opinions regarding nanotechnology have focused on the public's knowledge and views of risks and benefits [16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Some studies have shown a need for an understanding of the fundamental concepts of nanotechnology [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Public perceptions of nanotechnology were investigated through surveys distributed to a representative sample of a national population worldwide. Studies of public opinions regarding nanotechnology have focused on the public's knowledge and views of risks and benefits [16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Some studies have shown a need for an understanding of the fundamental concepts of nanotechnology [33][34][35].…”
Section: Introductionmentioning
confidence: 99%